A carga de doença por tuberculose no estado de Santa Catarina - Ferrer, Glênio César Nunes (2012)
Objective: To estimate the burden of disease due to tuberculosis in the State of Santa Catarina in the year 2009. Method: An epidemiological ecological study was carried out having as scope the State of Santa Catarina and its nine health macroregions. The study was composed by data of individuals residents in the State and reported in the Brazilian Mortality Database and the National Case Registry Database as confirmed cases of tuberculosis in 2009. The burden of disease indicator – DALY was estimated by the sum of the component of mortality - YLL and the component of morbidity - YLD. The YLL was estimated by the difference between the age of death and the standardized life expectancy, 80 years for men and 82.5 for women. A discount rate of 3% per year was applied. The YLD was estimated by the product of the weight of 0.271 by the disease duration of 18 months for HIV-negative cases and 12 months for HIV-positive cases using the incident cases in the year of study. To compensate for possible underreporting notification, a proportion of 60% of cases was increased in the notification data. In the cases of HIV/tuberculosis coinfection, a 17.7% of cases were increased. The absolute values of YLL, YLD and DALY were transformed into rates per 100,000 inhabitants, dividing them by the estimated population in the half of the studied period. It was observed the distribution of rates by sex, age and health macro-regions. Results: 4.446,29 YLLs were estimated generating a rate of 72.67 YLL/100,000 inhabitants. 1.197,98 YLDs were estimated generating a rate of 19.58 YLD/100,000 inhabitants. The burden of disease due to tuberculosis was estimated at 5.644,27 DALYs, which generated a rate of 92.25 DALY/100,000 inhabitants. The highest rates were found in males and in the age group of 30 to 44 and 45 to 59 years with uneven distribution by health macro-region. The highest burden was estimated in the Planalto Norte with 179.56 DALY/100,000 inhabitants followed by the Nordeste with 167.07 DALY/100,000 inhabitants. Conclusions: The burden of disease due to tuberculosis was concentrated in the adult age groups with variations in the health macro-regions, mainly in males. The use the indicator of burden of disease is recommended as an appropriate parameter for the evaluation of the uneven profile of priorities according to the burden of disease due to tuberculosis in the State of Santa Catarina.